2000
DOI: 10.3109/10428190009148848
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Immunophenotypes Detected by Flow Cytometry in Acute Lymphoblastic Leukemia

Abstract: The present study was designed to analyse the proportion of ALL patients in which the phenotypic detection of minimal residual disease (MRD) is feasible, based on the presence of aberrant phenotypes: lineage infidelity, asynchronous expression, overexpression and ectopic phenotype. For this purpose we have prospectively investigated the phenotype of blast cells from 25 patients at diagnosis using a large panel of monoclonal antibodies by multiparametric flow cytometry. The mean age was 23.3 +/- 17.3 with 10 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Using three or four colorcombinations, an aberrant,l eukemia-associated immunophenotype (LAIP)can be identifiedin90-95% of ALL samples (15,25). Garcia Ve la et alfound the coexistenceofatleasttwo aberrancies in leukemic lymphoblasts usingalarge panel of monoclonal antibodies (26). To our knowledge,the detection of across-lineage intracytoplasmic antigeninBCP ALL has not yetbeen published.…”
Section: Discussionmentioning
confidence: 99%
“…Using three or four colorcombinations, an aberrant,l eukemia-associated immunophenotype (LAIP)can be identifiedin90-95% of ALL samples (15,25). Garcia Ve la et alfound the coexistenceofatleasttwo aberrancies in leukemic lymphoblasts usingalarge panel of monoclonal antibodies (26). To our knowledge,the detection of across-lineage intracytoplasmic antigeninBCP ALL has not yetbeen published.…”
Section: Discussionmentioning
confidence: 99%
“…At present, these are the most sensitive techniques for MRD detection (one leukaemic cell/10 5 −10 6 normal cells), although molecular abnormalities are detectable only in a proportion of ALL patients (Biondi et al , 1992; Campana & Pui, 1995; Gibson et al , 1996; Heid et al , 1996; van Dongen et al , 1999; Foroni et al , 1999; Freeman et al , 1999; Hosler et al , 1999; Martuza et al, 2002). MRD detection by flow cytometry is based on the identification of leukaemia‐associated marker combinations, which are either not expressed or expressed at different levels of intensity by normal BM cells (Syrjälä et al , 1994; Campana & Pui, 1995; Jennings & Foon, 1997; Ciudad et al , 1998a; Campana & Coustan‐Smith, 1999; Griesinger et al , 1999; San Miguel et al , 1999; Garcia Vela et al, 2000; Porwit‐McDonald et al, 2000). A number of studies, using either flow cytometric or molecular approaches, showed that the presence of detectable MRD at any time point during the treatment course can predict relapse in childhood ALL (Biondi et al , 1992; Campana & Pui, 1995; Bear, 1998; Campana & Coustan‐Smith, 1999; van Dongen et al , 1999; Foroni et al , 1999; Griesinger et al , 1999; San Miguel et al , 1999; Coustan‐Smith et al, 2000; Pui & Campana, 2000; Radich, 2000; Sievers & Radich, 2000; Dworzak et al, 2002) and consequently current multicentre protocols have been designed on the basis of MRD monitoring.…”
mentioning
confidence: 99%
“…Leukemic cells display phenotypes that are either present in normal precursors or is unique for the leukemic population also referred to as leukemia‐associated immunophenotype (LAIP) or aberrant phenotype. Several publications described LAIP on blasts in acute leukemias (2–5). The major features are lineage infidelity and lineage promiscuity, where leukemic cells express antigens associated with a different cell line, e.g., CD13 and CD33 myeloid‐associated antigens in precursor‐B acute lymphoblastic leukemia (ALL) (6) or CD7 T‐cell marker expression in neoplastic myeloblasts (7).…”
mentioning
confidence: 99%